Tribology of Coated 316L SS by Various Nanoparticles - Dhiaa J. Aldabagh; Thair L. Alzubadi; Akram F. Alhuwaizi (International Journal of Biomaterials)
Background. Nanocoating of biomedical materials may be considered the most essential developing field recently, primarily directed at improving their tribological behaviors that enhance their performance and durability. In orthodontics, as in many medical fields, friction reduction (by nanocoatings) among different orthodontic components is considered a substantial milestone in the development of biomedical technology that reduces orthodontic treatment time. The objective of the current research was to explore the tribological behavior, namely, friction of nanocoated thin layer by tantalum (Ta), niobium (Nb), and vanadium (V) manufactured using plasma sputtering at 1, 2, and 3 hours on substrates made of 316L stainless steel (SS), which is thought to be one of the most popular alloys for stainless steel orthodontic archwires. The friction of coated 316L SS archwires coated with Ta, Nb, and V plasma sputtering is hardly mentioned in the literature as of yet. Results. An oscillating pin-on-plate tribological test using a computerized tribometer was performed by applying a load of 1 N for 20 minutes under the dry condition at room temperature (25°C) to understand their role in the tribological behavior of the bulk material. Ta and Nb were found to reduce the friction of their SS substrate significantly (45 and 55%, respectively), while V was found to deteriorate the friction of its substrate. Moreover, sputtering time had no substantial role in the friction reduction of coatings. Conclusions. Nanocoating of 316L SS bulk material by Nb and Ta with a 1-hour plasma sputtering time can enhance dramatically its tribological behavior. Higher coating hardness, smaller nanoparticle size, intermediate surface coating roughness, and lower surface binding energy of the coatings may play a vital role in friction reduction of the coated 316L SS corresponding to SS orthodontic archwires, predicting to enhance orthodontic treatment.